Relationship between Quality of Senior Nursing Students\' Caring Behaviors and Patients\' Satisfaction - Reza Negarandeh; Sepideh Mohammadi; Soheyla Zabolypour; Tajmohammad Arazi Ghojegh (Tehran University of Medical Sciences, 2012)
Background & Aim: Quality of nursing care is a major issue in nursing management. In the last year of nursing studies (internships) in Iran, nursing students are going to independently carry out responsibilities of graduated nurses. Patients&apos satisfaction is a main indicator for nursing care quality. This study was to determine the correlation between the quality of caring behaviors among internship students with the patients&apos satisfaction with nursing care quality. Methods & Materials: In this cross-sectional study, 200 patients were selected using convenience sampling method from the hospitals affiliated to the Tehran University of Medical Sciences. Data were gathered using two questionnaires including: 1) quality of the caring behaviors and 2) patient satisfaction with nursing care quality questionnaire (PSNCQQ). Data were analyzed using statistical tests in the SPSS-13. Results: Regarding quality of caring behaviors, the subscale scores of the knowledge and skills were good and patient education was low. The relationship between the nurses and patients, and nursing morality were in average level. Regarding the patient satisfaction, the highest level of satisfaction was related to nursing knowledge and skills and the lowest level was related to the patient education. Significant correlation was found between the total quality of the caring behaviors with the patients&apos satisfaction and their subscales (P<0.001). Conclusion: Based on the findings, patients are more satisfied with the caring behaviors of the students who focus on the communication with patients, nursing ethics, and especially patient education during the care.